Self-rated health according to sex and associated factors in Manaus, Brazil, 2019: a population-based cross-sectional study - Isabella Bagni Nakamura; Marcus Tolentino Silva; Taís Freire Galvão (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To assess the prevalence and factors associated with poor self-rated health according to respondents' sex in Manaus, Brazil. Methods: This was a cross-sectional population-based study with adults in Manaus in 2019. Adjusted prevalence ratios and 95% confidence intervals (95%CI) were calculated using Poisson regression following a hierarchical model. Results: Poor self-rated health occurred in 35.2% (95%CI 33.3;37.2) of the 2,321 participants and was higher in females (PR = 1.27; 95%CI 1.13;1.43). In the general population, among both sexes, poor self-rated health was higher among the oldest, those with moderate and severe food insecurity and with chronic diseases (p-value < 0.05). Among females, poor health was also higher among the evangelical and those with mild food insecurity. Among males, self-rated health was also poorer among the retired and those with education below elementary level (p-value < 0.001). Conclusion: The female sex had the poorest health rating, influenced by morbidity and access to food.